PROBLEMS IN USING GOOGLE CLASSROOM FACED BY EIGHT-GRADE STUDENTS OF MTS RAUDLATUL MUTA’ALLIMIN TEGALREJO - Muawanah, Imroatul; Irmayani, Irmayani; Zahro, Syifa' Khuriyatuz (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2024)
The era of the industrial revolution 5.0 increasingly developing technology, the learning process is directed to make good use of technology. so schools use online learning alternatives with various applications for students. one of them is using google classroom. This study discusses the student problems in using google classroom faced by eight-grade students of MTS Raudlatul Muta’allimin. This study aimed to describe the problems in using google classroom and to explain the strategies that face the problems of using google classroom. The participant of the research was VIII-A at MTS Raudlatul Muta’llimin. The research is descriptive qualitative and the research data were collected by two instrument research namely, questionnaire and interview. The finding of the study is there are several problems faced by students. The problem is divided into 2 factors, internal factors, and external factors. The problem in internal factors is during learning using google classroom, students are happy without being interested and motivated by learning google classroom and the student’s problem is difficulty on understand the material. The strategies of the problems in using google classroom delivered by the principial, the teachers and the students.